2003
DOI: 10.1002/cm.10148
|View full text |Cite
|
Sign up to set email alerts
|

Does axonemal dynein push, pull, or oscillate?

Abstract: Dynein is the molecular motor that provides motive force in cilia and flagella. Dynein is anchored to the A-subtubule of the outer doublets by a club-shaped extension called the stem, which supports the large globular head of the molecule. Dynein forms an attachment or cross-bridge to the B-subtubule of the adjacent outer doublet through a slender appendage extending from the head that is called the stalk or alternately the B-link. It is generally thought that the B-link mediates the interdoublet transfer of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…2 and 4, white arrowheads). It was proposed that linkage of heads to A-tubules may be important in force production (30). The tethering structures observed here might be one of the components that associate with dynein heavy chains, as proposed for Chlamydomonas dynein (31).…”
Section: Resultssupporting
confidence: 58%
“…2 and 4, white arrowheads). It was proposed that linkage of heads to A-tubules may be important in force production (30). The tethering structures observed here might be one of the components that associate with dynein heavy chains, as proposed for Chlamydomonas dynein (31).…”
Section: Resultssupporting
confidence: 58%
“…Following an analysis of the flexibility of the dynein stem, we proposed that force transmission between the doublets would be severely limited if there were not some mechanism to stabilize the dynein head during the power stroke (Lindemann & Hunt 2003). In addition, work from Warner's laboratory (Warner & Mitchell 1978, Zanetti et al 1979 showed beyond any doubt that the formation of rigor bridges physically reduces the size of Rigor and relaxed configurations of dynein.…”
Section: Seeing Is Believingmentioning
confidence: 99%
“…Progress is being made in this direction. Recently, some information on the elastic behavior of the dynein heavy chain has become available (Burgess et al, 2003;Lindemann and Hunt, 2003). Application of new techniques such as optical trapping and atomic force microscopy to cilia and flagella is expanding our knowledge of the mechanics of the axoneme (Shingyoji et al, 1998;Sakakibara et al, 1999Sakakibara et al, , 2004.…”
Section: Tests: Present and Futurementioning
confidence: 99%